PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SEJARAH - Nugroho, M. Gunawan Tarmudi; Pelu, Musa; Wahyuni, Sri (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The purpose of this research was to improve the creativity and historical learning outcomes in the XI IPS 2 class of SMA N 1 Kartasura in academic year 2017/2018 using Project Based Learning (PjBL) model and audiovisual media.This research was a classroom action research (CAR). The research was conducted in two cycles, each of which consisted of planning, acting, observing,and evaluation-reflection. The subject of research was XI IPS 2 class of SMA N 1 Kartasura, consisting of 36 students. Data source was obtained from teachers, students, and learning proces. The result of research showed that : (1) the application of the Project Based Learning (PjBL) model and audiovisual media could improve the creativity of the XI IPS 2 class of SMA N 1 Kartasura in academic year 2017/2018. It could be seen from the proportion of indicator achievement in the student creativity questionare and observation. The mean of achievement was 61,52 % in the cycle I and it increased to 70,11 % in cycle II, this gain had surpassed the specified target, 70%; (2) the application of the Project Based Learning (PjBL) model and audiovisual media could improve the historical learning outcome of the XI IPS 2 class of SMA N 1 Kartasura in academic year 2017/2018. It could be seen from the successfully passing value in the cognitive test result. The proportion of the of the students passing successfully passing successfully was 50,0% in cycle I and it increased to 69,55% in the cycle II, this gain had surpassed the specified target, 65%.